Attempts by the soviet regime to change the national identity of Lithuanians - Streikus, Arūnas (Genocidas ir rezistencija, 2007)
The article deals with the most important means used by the Soviet regime in order to change the national identity of the Lithuanians: the policy of historical memory and national-lin-guistic assimilation. With the help of documents from Soviet institutions and generalising previous historical research, an attempt is made to reveal the main directions of these efforts, and their aftermath.